Remote Ischemic Postconditioning for Ischemic Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jing-Jing Zhao; Hui Xiao; Wen-Bo Zhao; Xiao-Pei Zhang; Yu Xiang; Zeng-Jie Ye; Miao-Miao Mo; Xue-Ting Peng; Lin Wei (Chinese Medical Journal, 2018)
Background: Remote ischemic postconditioning (RIPostC) appears to protect distant organs from ischemia-reperfusion injury (IRI). However, cerebral protection results have remained inconclusive. In the present study, a meta-analysis was performed to compare stroke patients with and without RIPostC. Methods: CNKI, WanFang, VIP, CBM, PubMed, and Cochrane Library databases were searched up to July 2016. Data were analyzed using both fixed-effects and random-effects models by Review Manager. For each outcome, risk ratio (RR) and mean difference (MD) with 95% confidence interval (CI) were calculated. Results: A total of 13 randomized controlled trials that enrolled a total of 794 study participants who suffered from or are at risk for brain IRI were selected. Compared with controls, RIPostC significantly reduced the recurrence of stroke or transient ischemic attacks (RR = 0.37; 95% CI: 0.26–0.55; P < 0.00001). Moreover, it can reduce the levels of the National Institutes of Health Stroke Scale score (MD: 1.96; 95% CI: 2.18–1.75; P < 0.00001), modified Rankin Scale score (MD: 0.73; 95% CI: 1.20–0.25; P = 0.00300), and high-sensitivity C-reactive protein (MD: 4.17; 95% CI: 4.71–3.62; P < 0.00001) between the two groups. There was no side effect of RIPostC using tourniquet cuff around the limb on ischemic stroke treating based on different intervention duration. Conclusion: The present meta-analysis suggests that RIPostC might offer cerebral protection for stroke patients suffering from or are at risk of brain IRI.